A Review Paper On Unix - pal, Gajender; kumar, Kuldeep; kumar, Manish; GGN, DCE, (IJRDO -Journal of Computer Science Engineering, 2015)
Mach is a multiprocessor operating system kernel and environment under development at Carnegie Mellon University. Mach provides a new foundation for UNIX development that spans networks of uniprocessors and multiprocessors. This paper describes Mach and the motivations that led to its design. Also described are some of the details of its implementation and current status.